Hospital Frailty Risk Score predicts adverse events in older patients with vertebral compression fractures: Analysis of data in a nationwide in‐patient database in Japan. Issue 3 (31st January 2022) - Shimizu, Akio; Maeda, Keisuke; Fujishima, Ichiro; Kayashita, Jun; Mori, Naoharu; Okada, Kiwako; Uno, Chiharu; Shimizu, Miho; Momosaki, Ryo
Abstract : Aims: This study investigated the usefulness of frailty for predicting adverse events in patients with vertebral compression fractures (VCFs) during hospitalization using data obtained from the Japanese health insurance system. Methods: This retrospective cohort study of patients with VCFs aged ≥65 years was conducted using a nationwide database in Japan. We examined the relationships between frailty risk, classified using the Hospital Frailty Risk Score (HFRS), in‐hospital mortality, and complications such as pressure ulcers and pneumonia. Multivariate logistic regression analysis was used to estimate the association between the HFRS and the outcomes of patients with VCFs. Results: In this study, the data of 30 980 in‐patients with VCFs were analyzed. Of these patients, 76.8%, 21.3%, and 1.9% had low, intermediate, and high risks of frailty, respectively. The higher the risk of frailty, the higher the rate of in‐hospital mortality and the occurrence of all complications ( P  < 0.001 for trend). An intermediate risk of frailty was independently associated with in‐hospital mortality (odds ratio [OR], 1.421; P  < 0.001), whereas a high risk of frailty did not show statistical significance (OR, 1.385; P  = 0.150). Each frailty risk was independently associated with the occurrence of all complications during hospitalization. Conclusions: The HFRS, which can assess the risk of frailty based on routinely collected medical records, was predictive of adverse events in older patients with VCFs based on a nationwide database in Japan. Future studies need to assess approaches to preventing adverse events in frail VCF patients. Geriatr Gerontol Int 2022; 22: 233–239 .